Enhanced Recovery After Surgery for Pediatric Cleft Repair: A Systematic Review and Meta-Analysis. Issue 6 (7th September 2022) - Shin, Max; Wagner, Connor; Prasad, Aman; Barrette, Louis-Xavier; Chorath, Kevin; Moreira, Alvaro; Rajasekaran, Karthik
Abstract : Objective: Perform a systematic review assessing the efficacy of enhanced recovery after surgery (ERAS) protocols for cleft palate repair. Primary outcomes included hospital length of stay, readmission rates, and postoperative narcotic use. Secondary outcomes included complications, time to initial postoperative oral intake, and pain scores. Data Sources: Cohort and randomized studies of ERAS protocols pertaining to cleft palate repair were identified by systematic review of Medline, Scopus, Embase, and grey literature. Review Methods: Data extracted included patient demographics, clinical care protocols, complication rates, postoperative narcotic use, time to initial postoperative oral intake, hospital length of stay, family satisfaction, and 30-day readmission. Meta-analysis was used to compare outcomes between patients enrolled in ERAS protocols versus those in conventional care pathways. Results: Eight hundred sixty-five articles were screened, and 5 studies met full inclusion criteria. A total of 425 patients were included. Patients in ERAS protocols saw a mean reduction of – 23.96 hours in length of stay compared to controls (95% confidence interval [CI]: – 26.4, – 20.6). Patients in ERAS protocols also had decreased total morphine consumption (mean difference [MD]: – 3.88 mg; CI: – 4.31, – 3.45), and decreased time to first initial feed compared to controls (MD: – 3.88 hours; CI: – 4.3, – 3.5). There was no difference in readmission rates or complication rates between ERAS and control groups. Conclusions: ERAS protocols have seen limited use in pediatric patients. The present study sought to assess the impact of ERAS protocols following primary palatoplasty. Our results indicate decreased hospital length of stay, postoperative opioid consumption, and time to feeding, without increasing readmission rates or complication rates.